Iron bean delivery program in Rwanda - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
By the end of 2018, an estimated 20% of beans produced in Rwanda were of iron varieties, with 15% of the population, i.e., 1.8 million beneficiaries, consuming them. These varieties provide 80% of daily iron needs. Iron bean yields were about 20% higher than other beans.